Primary uterine rhabdomyosarcoma: a unique presentation - Padore, Ishaan Sachin; Padore, Archna Sachin; Shetye, Rahi R.; Shetye, Vedha R.; Padore, Sachin S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine rhabdomyosarcoma in adults is extremely rare. We present the case of a 61-year-old P1L1 postmenopausal female who came with abdominal distension and pedal edema since, 20 days. The typical presentation of post-menopausal bleeding was absent in this patient. The clinical presentation, massively raised CA 125 levels and CT findings pointed towards an ovarian malignancy. USG and MRI leaned towards carcinoma endometrium. The final diagnosis was clinched on immunohistochemical studies. The tumor had an aggressive course with a fatal outcome within days.